The 21st-century hipster: On micro-populations in times of superdiversity. (December 2016) - Maly, Ico; Varis, Piia
Through a critical review of existing literature on hipsters, and an analysis of online data, this article provides a description of 'hipster culture'. To this end, we examine the reoccurring markers of hipster identity and, crucially, the accompanying identity discourses on hipsters. As a result, a picture of hipster culture emerges as a translocal and layered phenomenon with contextually specific claims to authenticity, and certain material infrastructures and effects emerge with the culture. Finally, we will propose the concept of 'micro-population' as a tool for making sense not only of hipsters, but identity in general in times of superdiversity.